REPRESENTASI TOXIC RELATIONSHIP DI VIDEO KLIP RED VELVET "PSYCHO" (KAJIAN SEMIOTIKA ROLAND BARTHES) - Azlia Zaafira Disyacitta (2023)
Music and video clips are one of the media for conveying messages. Red Velvet, a girl group from South Korea, performed a song with the theme of toxic relationships. Toxic relationships often occur because a strong patriarchal culture often causes disputes in relationships. The theme of toxic relationships is relevant to listen to because the phenomenon of toxic relationships is still widespread in Indonesia. This research aims to determine the representation of toxic relationships contained in the video clip "Psycho" by Red Velvet based on the meaning of denotation, connotation and myth. This research uses a descriptive qualitative approach with a constructivism paradigm and Roland Barthes' semiotic method. The concept used is Eight Types of Toxic Relationship Behavior by Thomas Lillian Cory, Ph.D. The results of this research are that the video clip "Psycho" by Red Velvet is verified to contain representations of behavior that is often found in a toxic relationship. Toxic relationships occur not only in couples but also in friendships. The storyline of the video clip depicts Red Velvet as perpetrators and victims who find it difficult to get out of a toxic relationship until they have the courage to take action and end bad friendships and romantic relationships. The meaning of this video clip shows forms of behavior that lead to toxic relationships so that they can be avoided and ended.